Epidural Analgesia During the Second Stage of Labor: A Randomized Controlled Trial. Issue 5 (November 2017) - Shen, XiaoFeng; Li, Yunping; Xu, ShiQin; Wang, Nan; Fan, Sheng; Qin, Xiang; Zhou, Chunxiu; Hess, Philip E.
Abstract : OBJECTIVE: To evaluate whether maintaining a motor-sparing epidural analgesia infusion affects the duration of the second stage of labor in nulliparous parturients compared with a placebo control. METHODS: We conducted a double-blind, randomized, placebo-controlled trial involving nulliparous women with term cephalic singleton pregnancies who requested epidural analgesia. All women received epidural analgesia for the first stage of labor using 0.08% ropivacaine with 0.4 micrograms/mL sufentanil with patient-controlled epidural analgesia. At the onset of the second stage of labor, women were randomized to receive a blinded infusion of the same solution or placebo saline infusion. The primary outcome was the duration of the second stage of labor. A sample size of 200 per group (400 total) was planned to identify at least a 15% difference in duration. RESULTS: Between March 2015 and September 2015, 560 patients were screened and 400 patients (200 in each group) completed the study. Using an intention-to-treat analysis, the duration of the second stage was similar between groups (epidural 52±27 minutes compared with saline 51±25 minutes, P =.52). The spontaneous vaginal delivery rate was also similar (epidural 193 [96.5%] compared with saline 198 [99%], P =.17). Pain scores were similar between groups at each measurement during the second stage. More women who received placebo reported satisfaction scores of 8 or less (epidural 32 [16%] compared with saline 61 [30.5%], P =.001). CONCLUSION: Maintaining the infusion of epidural medication had no effect on the duration of the second stage of labor compared with a placebo infusion. Maternal and neonatal outcomes were similar. A low concentration of epidural local anesthetic does not affect the duration of the second stage of labor. CLINICAL TRIAL REGISTRATION: Chinese Clinical Trial Register, http://www.chictr.org.cn/enindex.aspx, ChiCTR-IOR-15005875. Abstract : Maintaining an infusion of epidural medication does not prolong the second stage of labor compared with maintaining a placebo saline infusion.